Association of proton pump inhibitor and histamine H2-receptor antagonists with restless legs syndrome. Issue 4 (29th October 2020) - Earley, Eric J; Didriksen, Maria; Spencer, Bryan R; Kiss, Joseph E; Erikstrup, Christian; Pedersen, Ole B; Sørensen, Erik; Burgdorf, Kristoffer S; Kleinman, Steven H; Mast, Alan E; Busch, Michael P; Ullum, Henrik; et al.
Abstract: Restless legs syndrome (RLS) is a common sensorimotor disorder, which can disrupt sleep and is thought to be caused in part by low cellular iron stores. Proton pump inhibitors (PPI) and histamine H2 -receptor antagonists (H2 A) are among the most commonly used drugs worldwide and show evidence of causing iron deficiency. We conducted a case/non-case observational study of blood donors in the United States ( N = 13, 403; REDS-III) and Denmark ( N = 50, 323; Danish Blood Donor Study, DBDS), both of which had complete blood count measures and a completed RLS assessment via the Cambridge–Hopkins RLS questionnaire. After adjusting for age, sex, race, BMI, blood donation frequency, smoking, hormone use, and iron supplement use, PPI/H2 A use was associated with RLS (odds ratio [OR] = 1.41; 95% confidence interval [CI], 1.13–1.76; p = 0.002) in REDS-III for both PPI (OR = 1.43; CI, 1.03–1.95; p = 0.03) and H2 A (OR = 1.56; CI, 1.10–2.16; p = 0.01). DBDS exhibited a similar association with PPIs/H2 As (OR = 1.29; CI, 1.20–1.40; p < 0.001), and for PPIs alone (OR = 1.27; CI, 1.17–1.38; p < 0.001), but not H2 As alone (OR = 1.18; CI, 0.92–1.53; p = 0.2). We found no evidence of blood iron stores mediating this association. The association of PPI, and possibly H2 A, consumption with RLS independent of blood iron status and other factors which contribute to RLS risk suggest the need to re-evaluate use of PPI/H2 A in populations at particular risk for RLS.